Peran Pendidikan Islam Dalam Melawan Radikalisme Melalui Moderasi Beragama - Agustin sri ningsih; Jumiarti Hurairah; Muji rahayu (Al-Abshor : Jurnal Pendidikan Agama Islam, 2024)
In Indonesia, Islamic education is very important to fight radicalism and promote religious moderation. The Ministry of Religion emphasizes the importance of religious education in the school curriculum with a focus on harmonizing intellectual and spiritual knowledge. The importance of the campaign for a moderate understanding of Islam is demonstrated by the horizontal conflict caused by radicalism and intolerance. Responsible for spreading proper understanding of Islamic concepts such as tolerance, jihad, and monotheism are Islamic teachers and educators can educate the next generation to appreciate multicultural life. Madrasas and Islamic boarding schools function as Islamic institutions that teach moderate values. To deal with radicalism, educational institutions, parents, communities and the government must work together. Islamic education can build a tolerant, critical and moderate understanding of religion if implemented correctly. This will encourage increased faith. Abstrak Di Indonesia, pendidikan Islam sangat penting untuk melawan radikalisme dan mempromosikan moderasi beragama. Kementerian Agama menekankan pentingnya pendidikan agama dalam kurikulum sekolah dengan fokus pada penyelarasan pengetahuan intelektual dan spiritual. Sangat pentingnya kampanye pemahaman Islam yang moderat ditunjukkan oleh konflik horizontal yang disebabkan oleh radikalisme dan intoleransi. Bertanggung jawab atas penyebaran pemahaman yang tepat tentang konsep Islam seperti toleransi, jihad, dan tauhid adalah guru dan pendidik Islam. Pendidikan karakter yang inklusif dapat mendidik generasi berikutnya untuk menghargai kehidupan multikultural. Madrasah dan pesantren berfungsi sebagai lembaga  Islam yang mengajarkan tentang nilai-nilai moderat. Untuk menghadapi radikalisme, lembaga pendidikan, orang tua, komunitas, dan pemerintah harus bekerja sama. Pendidikan Islam dapat membangun pemahaman yang toleran, kritis, dan moderat tentang agama jika diterapkan dengan benar. Ini akan mendorong peningkatan iman